Conductivity studies of schiff base ligands derived from o-phenylenediamine and their Co(II) and Zn(II) complexes / Muhamad Faridz Osman and Karimah Kassim - Osman, Faridz; Kassim, Karimah (Institute of Research Management and Innovation (IRMI), 2015)
The coordination complexes of Co(II) and Zn(II) with Schiff bases derived from o-phenylenediamine and substituted 2-hydroxybenzaldehyde were prepared. All compounds were characterized by Fourier transform infrared (FTIR) spectroscopy and Nuclear magnetic resonance (NMR) spectroscopy elemental analyzers. They were analyzed using impedance spectroscopy in the frequency range of 100HZ-1MHz. L1 and L2 showed higher conductivity compared to their metal complexes, which had values of 1.37 x 10-⁷ and 6.13 x 10-⁸ S/cm respectively.